2010
DOI: 10.1177/0730888409352064
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Discretionary Work Effort

Abstract: Do men and women differ in the extent to which they work beyond the level required by their jobs? Does this gender difference vary across national contexts? The authors answer these questions using survey data from the United States and Britain. Multivariate ordered logistic regression models reveal no gender difference in self-reported discretionary effort in the United States, but greater discretionary effort among women in Britain, net of individual, family, and workplace characteristics. The authors attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 129 publications
(143 reference statements)
1
17
1
Order By: Relevance
“…Social role theory highlights that gender role beliefs are formed within a particular society's circumstances and culture (Eagly & Wood, 2012). Indeed, empirical evidence has suggested that contemporary cultural gender roles, expectations and state of gender equality may influence workplace behaviours differently in different countries (Kmec & Gorman, 2010). Therefore, future research might explore whether gender-related effects on knowledge hiding apply similarly across different cultural contexts.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Social role theory highlights that gender role beliefs are formed within a particular society's circumstances and culture (Eagly & Wood, 2012). Indeed, empirical evidence has suggested that contemporary cultural gender roles, expectations and state of gender equality may influence workplace behaviours differently in different countries (Kmec & Gorman, 2010). Therefore, future research might explore whether gender-related effects on knowledge hiding apply similarly across different cultural contexts.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…This is the result of three factors that have contributed to the professional development of women in the hospitality industry. First, the growth of the sector itself has enabled women to increase both their numbers and visibility in operational and management level positions (Kmec & Gorman, 2010). Furthermore, it is estimated that women represent more than 50% of the work force in the hotel sector (Eurostat, 2018;UNWTO, 2018).…”
Section: Gender In the Hospitality Industrymentioning
confidence: 99%
“…In Piore’s [ 17 ] classic writing about the “dual labor market,” for example, he suggests that people relegated to the secondary labor market, where jobs are insecure and lacking long-term prospects, learn not to value certain behavior, such as reliably showing up to work or exerting more work effort than required, because the secondary labor market does not reward such behavior. More recently, Kmec and Gorman [ 3 ] show that workers with more autonomous and secure jobs, which are likely in the primary labor market, report higher levels of discretionary work effort. Their finding echoes Piore’s argument that workers’ tendency to exert extra work effort is often responsive to structural characteristics of their jobs.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the potential importance of working conditions, few studies have comprehensively addressed which conditions are particularly relevant to individuals’ discretionary work effort or whether different groups of workers respond to the various conditions differently. In rare studies where researchers do investigate the roles of job and workplace characteristics [e.g., 3 ], they generally rely on cross-sectional comparisons of self-reported effort. Such comparisons cannot rule out the possibility that certain unobserved factors, such as people’s upbringings, value systems, and personality traits, simultaneously sort them to different types of jobs and determine their willingness to exert much effort at work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation